A comparative study of spousal abuse in rural and urban communities: A case of Lafia Local Government Area, Nasarawa State - Sunday Adesina Ayesoro; Stephen Sunday Ojo; Deborah Ibechone Peter (Journal of Social, Humanity, and Education, 2025)
Purpose: The study is to consider the rural and urban dimension of the problem with a view to proffering sustainable and applicable solutions to the problem. Methodology/approach: The research design of this study was survey-based. A stratified random selection strategy was used to choose a representative sample of 100 married women in the study area. Instrument used was self-administered questionnaire and Focus Group Discussion (FGD) and analyzed through content analysis and descriptive statistics. Results/findings: The findings revealed that the prevalence of spousal abuse is higher in rural areas than in urban areas, as indicated by 70% of the respondents. Also, 68% from rural area and 60% from urban area strongly agreed that women's economic standing and educational attainment are related to the occurrence of spousal abuse in every given location. Conclusion: The study concludes that illiteracy, ignorance, and women’s economic dependence significantly contribute to the higher prevalence of spousal abuse in rural communities. Women empowerment and education are essential to mitigating this issue. Limitations: The study is limited to comparison between the prevalence of spousal abuse in rural and urban communities without considering personal factors. Contribution: The study contributes to knowledge in the area of identify the factors that causes variation in the prevalence of spousal abuse in rural and urban communities in the context of socio-economic development in Lafia Local Government area of Nasarawa state. This will add to literature in the field of gender relations and women development.